The Use of Learning Methods in Learning History During the Covid-19 Pandemic - Hiskiya, Frensen S; Sarkadi; Ibrahim, Nurzengky (Journal of Education Reseach and Evaluation, 2023)
During the Covid-19 pandemic, online learning was carried out so that learning had to be done from home to break the Covid-19 chain. This study aims to analyze the use of the history learning method used during the Covid-19 pandemic. The research method used was descriptive qualitative. By using a case study approaches so that data collection in the research process uses observation, interviews, and documentation techniques. Furthermore, the data and sources of this research data come from the schools studied. The results of the study found that several history learning methods were used during the Covid-19 pandemic, such as the audiovisual method, the indirect learning method, the project method, and the group work method. This learning method is most often used by teachers in conducting history lessons during the Covid-19 pandemic. By using various learning methods in learning history, students are very happy because the method used is not boring during learning hours by using learning methods and materials carried out by the teacher, students are also very quick to understand the material conveyed by the teacher in carrying out learning.